Nanoskalige Analytik der Mikrostruktur von hochdosig bestrahltem Beryllium - Zimber, Nikolai (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2022)
The aim of the present work is to develop an in-depth understanding of the microstructural changes in neutron-irradiated beryllium. In particular, it aims to reveal the precise mechanisms leading to the observed tritium retention.Both, helium and tritium could be detected for the first time by high-resolution electron energy loss spectroscopy (EELS) within bubbles in the grain interior as well as along grain boundaries.